P54 Mapping the prevalence and nature of drug related problems among hospitalised children in the United Kingdom: a systematic review. Issue 9 (19th August 2020) - Sutherland, Adam; Phipps, Denham; Tomlin, Steve; Ashcroft, Darren
Abstract : Aims: Problems with medication account for 10–20% of all adverse healthcare events in the NHS, costing between £200–400 million per year. 1 Children are more likely to experience medication related harm. 2 International reviews of the prevalence of drug-related problems are over ten years old. 3 There is a need for a focussed and critical review of the prevalence and nature of drug-related problems in hospitalised children in the UK to support the development and targeting of interventions to improve medication safety. 4 Methods: Nine electronic databases (Medline, Embase, CINAHL, PsychInfo, IPA, Scopus, HMIC, BNI, The Cochrane library and clinical trial databases) were searched from January 1999 to September 2018. Studies were included if they were based in the UK, reported on the frequency of adverse drug reactions (ADRs), adverse drug events (ADEs) or medication errors (MEs) affecting hospitalised children, and quality appraisal of the studies was conducted. Results: 26 studies were included; none of which specifically reported on the prevalence of ADEs. Three ADR studies reported a median prevalence of 28.3% of patients (IQR 13); >70% of reactions warranted withdrawal of medication. Sixteen studies reported on prescribing errors and the median prescribing error rate in all paediatric contexts was 10.7% of prescriptions (IQR 6) Seven studies explored prescribing errors in PICU and the prevalence was twice that in non-ICU areas (11.1% prescriptions; IQR 2.9 versus 6.5% prescriptions; IQR 4.3). The median rate of dose prescribing errors was 11.1% doses prescribed (IQR 10.6). Four studies reported administration errors of which three used consistent methods. Across these three studies, a median prevalence of 12.4% of administrations (IQR 7.3) was found. Administration technique errors represented 53% of these errors (IQR 14.7). Errors detected during medicines reconciliation at hospital admission affected 43% of patients, 33% (IQR 13) of prescribed medication with 70.3% (IQR 14) classified as potentially harmful. Medication errors detected during reconciliation on discharge from hospital affected 33% of patients and 19.7% of medicines, with 22% considered potentially harmful. No studies examined the prevalence of monitoring or dispensing errors. Conclusions: Children are commonly affected by drug-related problems throughout their hospital journey. Given the high prevalence and risk of patient harm, there is an urgent need for outcome-focussed research on preventable ADEs in paediatric hospital settings in the UK. A deeper understanding of medication processes for children in hospital from a systems and theoretical perspective will also support the development and tragetting of effective interventions to improve patient safety. References: Chief Medical Officer. An Organisation With a Memory. London ; 2000. Kaushal R, Bates DW, Landrigan C, et al . Medication errors and adverse drug events in pediatric inpatients. JAMA 2001;285 :2114–2120. Ghaleb MA, Barber N, Franklin BD, Yeung VWS, Khaki ZF, Wong ICK. Systematic review of medication errors in pediatric patients. Ann Pharmacother 2006;40 :1766–1776.